Effect of plumage colour and estimation of variance components of bi-weekly growth traits in Japanese quail (Coturnix coturnix japonica) - DASH, SHAKTI KANT; NAIK, SWAYAMPRABHA; DUBEY, PREM PRAKASH; MALHOTRA, PUNEET; BANSAL, BALJINDER KUMAR (The Indian Journal of Animal Sciences, 2018)
The present investigation was undertaken in black and white quails for studying the effect of plumage colour,estimating genetic parameters and fitting non-linear regression model to growth curve in white and black Japanese quails. White quails were significantly heavier in comparison to black quails across age groups indicating association of plumage colour with growth rate. The body weight variables measured at bi-weekly intervals when considered as a single variable had low repeatability indicating they were genetically not identical variables. Paternal half-sib estimates of heritability indicated higher additive variance in white quails in comparison to black quails. Phenotypiccorrelation estimates between bodyweights at 2, 4, 6, 8 and 10 weeks of age, ranged from medium to high indicating favourable correlated response in bodyweight variables. Gompert curve had very good fit with the data (99.6%) and similar curve parameters were estimated in both quail varieties. Point of inflection (IPT) was similar in both quail varieties and was 3.46 (black) and 3.44 weeks of age (white). The estimates of different growth parameters indicated the favourable effect of selection in these quail lines. Results indicated that growth curve estimates can be used for developing future breeding strategies in quails.